Biodegradation of cyanide by cyanide dihydratase from locally isolated Serratia marcescens isolate AQ07 - Ibrahim, Karamba Kabiru (2016)
Cyanide is a very toxic chemical and is one of the environmental pollutants found in sewage. Serratia marcescens isolated from soil sample around Universiti Putra Malaysia (3˚00’23.91"N, 101˚42’31.45"E) was found to have cyanide degrading capability. Spectrophotometric method was used to examine the biodegradation ability of the bacteria in free and immobilised forms using cyanide incorporated buffer medium. Factors affecting cyanide biodegradation such as carbon and nitrogen sources, pH of medium, inoculums size, cyanide concentration and temperature were optimised using one factor at time and response surface methods. Cyanide tolerance and effect of heavy metals (silver, arsenic, cadmium, cobalt, chromium, copper, mercury, nickel, lead and zinc) were investigated. The results illustrates that glucose at 5.5 g/L, yeast extract at 0.55 g/L, pH 6, 20% inoculums size, 200 mg/L cyanide concentration and 32.5ºC are the optimum biodegradation conditions required by the bacteria. Immobilised form of the bacteria showed better biodegradation in terms of duration as it degrades the cyanide in 24 hours compared to free cells that require 72 hours degradation process. The bacteria can tolerate 700 mg/L cyanide concentration in free cells and 900 mg/L in immobilised forms. Heavy metals tested at 1 ppm illustrates that the bacteria could stand their effect with the exception of mercury, which degraded only 24.7% in free cells and 61.6% in immobilised forms. Enzyme activity assay illustrates that the bacteria follow the hydrolytic pathway catalysed by cyanide dihydratase to degrade the cyanide. The purified enzyme was able to detoxify 82% of 2 mM potassium cyanide in 10 min of incubation and the rate of cyanide depletion improved linearly as the enzyme concentration is increased. Hydrolysis of cyanide by the purified enzyme fits Michaelis-Menten saturation kinetics when examined over cyanide concentration of 5 mM potassium cyanide. Lineweaver-Burk plot revealed a linear response at 5 mM KCN and less. Michaelis-Menten constant (Km) for best-fit values of 26.52 and Vmax value of 1.13 and R2 value of 0.9 were determined. Total enzyme activity for crude extract stands at 79.9 and 49, 880 mg/L total protein. After final purification process, the total enzyme activity stands at 0.165 with a total protein of 52 mg/L demonstrating yield of 0.207% and purification fold of 65.78. Effect of pH and temperature revealed that enzyme activity was most active at pH of 8 and temperature of 27ºC. The temperature stability test carried out on the enzyme illustrated that it was stable for 70 days at – 20ºC and when stored at 4ºC, the stability starts reducing after 4 days of incubation. Furthermore, SDS-PAGE electrophoresis post purification revealed the molecular weight of the enzyme to be ~38 kDa, which is a further affirmation. Serratia marcescens isolate AQ07 was observed to have the ability to degrade cyanide. Suitable growth and biodegradation conditions were obtained using the optimisation methods. It demonstrates that immobilised cells of the bacteria have a greater ability for cyanide biodegradation compared to free cells, which can be applied for cyanide treatment in sewage. It has been registered in the gene bank as isolate AQ07 with assigned accession number KP213291